Early Extubation in Children after Cardiac Surgery. Initial Experience from a Tertiary Care Hospital in Mexico City - Figueroa-Solano, Javier; Infante-Sánchez, Karen; Espinosa-Guerra, Kenia; Astudillo-De Haro, Esteban David; Martínez-Albarenga, Paola María; Lesprón-Robles, Ma del Carmen; Molina-Méndez, Francisco Javier; Miranda-Chávez, Irma Ofelia (Journal of Pediatric Intensive Care, 2022)
Early extubation (EE) in pediatric cardiac surgery has demonstrated important benefits. However, ventilating them for 24 hours or more (delayed decannulation, DD) is an enduring practice. The objectives of this study were to describe the clinical profiles of EE in our setting and analyze its impact and the factors that prolong mechanical ventilation. Children operated on for cardiac surgery from 2016 to 2017 were included. Data were obtained from an electronic database. Comparisons were performed with Pearson's chi-square test, Student's t-test, or Mann–Whitney U test. Multivariate logistic regression was used to evaluate factors associated with DD. Of 649 cases, 530 were extubated on one occasion. EE was performed in 305 children (57.5%): 97 (31.8%) in the operating room and 208 (68.2%) in the intensive care unit (ICU). Reintubation (RI) occurred in 7.5% with EE and 16.9% with DD (p = 0.001). Fewer complications and ventilation time and decreased ICU and hospital length of stay resulted with EE. Age, presurgical ventilation, emergency surgery, pump time, attempts to weaning from cardiopulmonary bypass, bleeding greater than usual, and CPR in surgery were associated with DD. EE in the National Institute of Cardiology (INC; Spanish acronym) is in the middle category and has shown benefits without compromising the patient; the fear of further complications, RI, or death is unfounded. Although not all children at the INC can be decannulated early, if there are no or minimal risk factors, it should be a priority.
Keywords: early extubation; pediatric cardiac surgery